Enhancing the Bioavailability of Noni Fruit (Morinda citrifolia L.) Through Nanotechnology as a Topical Anti-Aging Formulation - Sari, Erlinda Novita; Wikantyasning, Erindyah Retno; Utami, Wahyu (FORIKES, 2026)
Premature aging reduces collagen production and activates MAPK and MMPs pathways. Continuous use of retinol may cause adverse effects; therefore, natural ingredients are recommended as alternative therapies. Noni fruit (Morinda citrifolia L.) has potential anti-aging properties; however, its polyphenolic compounds are sensitive and exhibit limited skin absorption. The application of nanotechnology may address these bioavailability challenges. This review aimed to identify, analyze, and provide evidence regarding the enhancement of bioavailability of Indonesian herbal plants through nanotechnology-based topical formulations for managing skin aging. A systematic literature review was conducted by searching accredited national and international journals indexed in Google Scholar using the keywords “Aging,” “Morinda citrifolia L.,” and “Nano” from 2014 to 2024. From 2,950 identified articles, 80 met the inclusion criteria. The findings indicate that noni fruit contains diverse bioactive compounds with significant anti-aging potential. It is rich in vitamin C, flavonoids, and phenolic compounds. Nanoparticle formulations of noni fruit enhance its anti-aging efficacy through multiple mechanisms and improve the permeation of active compounds into the skin. In conclusion, noni fruit demonstrates strong potential as a topical anti-aging agent, and its limitations can be overcome through nanoparticle-based technology, thereby increasing its therapeutic, functional, and economic value.Keywords: aging; Morinda citrifolia L.; nanotechnology